Discrimination between cells of murine and human origin in xenotransplants by species specific genomic in situ hybridization - Steck, Eric; Burkhardt, Michaela; Ehrlich, Hermann; Richter, Wiltrud (Xenotransplantation, 2010)
Steck E, Burkhardt M, Ehrlich H and Richter W. Discrimination between cells of murine and human origin in xenotransplants by species specific genomic in situ hybridization. Xenotransplantation 2010; 17: 153-159. © 2010 John Wiley & Sons A/S. Abstract: Xenotransplantation of human cells into immune compromised host species is an important experimental setup to follow the faith of implanted cells and the contribution of host cells to tissue regenerates. In this context, it is of major relevance to discriminate between transplanted and host cells. Labeling techniques of donor cells frequently reach only part of the cells, have the risk of influencing their natural biological activity and may allow label transmission to host cells via vesicles or phagocytosis. To allow positive detection of donor and host cells on histological sections of a transplant, we have developed a method to identify mouse cells by in situ hybridization of murine specific genomic repetitive elements (SINE/B1, SINE/B2) which we combined with human cell detection using Alu in situ hybridization. We describe generation of mouse specific probes, hybridization and read out using biomaterial supported human chondrocyte constructs implanted subcutaneously in mice. Mouse specific genomic repeats identified attached or invaded host cells in the transplants with human specific signals confined to regions of cartilage-like extracellular matrix. The method is suitable to discriminate specifically between cells of human and mouse origin without overlap of unspecific staining.